Technological innovations and sustainability transitions in the bioeconomy: A multiscalar approach toward the development of bioclusters - David Ayrapetyan (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2023)
The bioeconomy offers solutions to urgent sustainability challenges, such as climate change, resource scarcity, and world hunger. Bioclusters, which are localized hubs of bioeconomy activities, can create synergies in the use of natural resources and new technological knowledge, thereby providing fertile ground for sustainability transitions and technological innovations in the bioeconomy. Following an interdisciplinary perspective, this dissertation adopts a multiscalar view toward bioclusters to link them with broader contexts and study their role in the bioeconomy transition. By employing quantitative and qualitative methodologies, I analyze the technological and ecological development of the French Bazancourt-Pomacle biocluster. The results reveal the dynamics and interrelations among specific scales and levels linked to positive ecological and technological outcomes, providing valuable insights for policymakers and managers aiming to advance the bioeconomy. – – Die Bioökonomie bietet Lösungen für dringende Nachhaltigkeitsprobleme wie den Klimawandel, Ressourcenknappheit und Welthunger. Biokluster, als lokalisierte Zentren für bioökonomische Aktivitäten, können durch Synergien in der Nutzung natürlicher Ressourcen und neuer technologischer Kenntnisse einen fruchtbaren Boden für Nachhaltigkeitsübergänge und technologische Innovationen in der Bioökonomie schaffen. In dieser Dissertation wird mit einem interdisziplinären Ansatz und multiskalaren Perspektive die Rolle von Biokluster im Übergang zur Bioökonomie untersucht. Durch den Einsatz quantitativer und qualitativer Methoden analysiere ich die technologische und ökologische Entwicklung des französischen Bioklusters Bazancourt-Pomacle. Die Ergebnisse zeigen die Dynamik zwischen spezifischen Skalen und Ebenen im Zusammenhang mit positiven ökologischen und technologischen Ergebnissen auf und liefern wertvolle Erkenntnisse für Entscheidungsträger, die die Bioökonomie vorantreiben möchten.
urn:nbn:de:gbv:3:4-1981185920-1128581
Keywords: 330